Anatomical description of retromolar foramina in dry human mandibles: incidence, morphometry, and topography - Luiz Felipe PALMA; Leonardo Augusto LOMBARDI (Faculdade São Leopoldo Mandic, 2018)
Objective: To carry out morphometric, topographic, incidence analysis of retromolar foramina in dry adult human mandibles, and relate the findings to Dental practice. Methods: 265 mandibles were evaluated simultaneously by two researchers. With the aid of metal wires, each retromolar foramen was classified regarding diameter. Foramina with a diameter smaller than 0.5mm were not taken into account. Results: Retromolar foramina were observed in 23.4% of cases, with a higher bilateral incidence (with distinction of both antimeres), and up to 4 of them located in the same mandible. Furthermore, most foramina had a diameter between 0.5 and 1mm. Conclusion: The retromolar foramina are clinically relevant findings and should never be underestimated by clinicians.